Low-Distortion Switching Amplifier with Discrete-Time Click Modulation - Stefanazzi, Leandro (2014)
An all-digital Class-D amplifier based on a discrete time implementation of the click modulator is presented. The algorithm is able to generate binary signals with separated baseband, displacing the harmonic content produced by the modulation process above certain frequency chosen by the designer. Perfect demodulation can be achieved by a simple low-pass filter. Previous implementations of the discrete-time click modulator reported in the literature suffer from aliasing in the frequency domain. The approach proposed here avoids aliasing, without the necessity to increase (interpolate) the sampling frequency of the signals. Following a brief theoretical introduction, the performance of the proposed architecture is demonstrated by experimental measurements performed on an H-bridge amplifier. An 88 dB SNR and a THD+N less than 0.04 % is attainable over the entire audio band, extending from 20 Hz up to 20 kHz; on the other hand, no traces of IMD appear above the predicted noise floor. These performance indices are obtained for switching rates as low as 40 kHz. The reduction of the switching frequency provides more flexibility for the design of the demodulation stage allowing to trade off between the complexity of the demodulation filter and the achievable efficiency of the switching stage.